2016
DOI: 10.1371/journal.pone.0159925
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Fatality during the Intensive Phase of Anti-Tuberculosis Treatment

Abstract: ObjectiveTo determine the case-fatality rate (CFR) at the end of the intensive phase of tuberculosis (TB) treatment, and factors associated with fatality.MethodsTB patients diagnosed between 2006 and 2013 were followed-up during treatment. We computed the CFR at the end of the intensive phase of TB treatment, and the incidence of death per 100 person-days (pd) of follow-up. We performed survival analysis using the Kaplan-Meier method and Cox regression, and calculate hazard ratios (HR) and 95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
9
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
5
9
1
3
Order By: Relevance
“…First important finding of current study was the higher rate of mortality in PTB patients i.e., 13.5%, whereas most of the other studies reported the lower mortality prevalence than current study such as Asgedom SW et al, 11.3%,17 Shahrezaei M et al, 1.6%,18 and Rodrigo T et al, 3.5% 19. Another study by Takarinda KC et al reported the higher prevalence of mortality 22.0% in TB patients 20.…”
Section: Discussioncontrasting
confidence: 44%
“…First important finding of current study was the higher rate of mortality in PTB patients i.e., 13.5%, whereas most of the other studies reported the lower mortality prevalence than current study such as Asgedom SW et al, 11.3%,17 Shahrezaei M et al, 1.6%,18 and Rodrigo T et al, 3.5% 19. Another study by Takarinda KC et al reported the higher prevalence of mortality 22.0% in TB patients 20.…”
Section: Discussioncontrasting
confidence: 44%
“…A medida que aumenta la edad se incrementa el riesgo de fallecer por TB, esto puede deberse a comorbilidades y al declive natural de la inmunidad, la respuesta inmunitaria se va deteriorando y esto contribuye a la reactivación de la TB latente, lo que hace más propensos a desarrollar la enfermedad. Esto, sumado al diagnóstico tardío, aumenta la posibilidad de un desenlace fatal (22, 23).…”
Section: Discussionunclassified
“…Admission to a hospital with an ER on site was a highly relevant risk predictor for death, suggesting there can be barriers to accessing care and to adequate and timely treatment at the outpatient clinics, as would be expected due to certain limitations at these facilities versus hospitals. The start of treatment could therefore be delayed, possibly leading to a more severe case of TB, which, in turn, would increase the chance of complications that could affect mortality (29).…”
Section: Discussionmentioning
confidence: 99%